PERLINDUNGAN HUKUM BAGI PEKERJA MIGRAN INDONESIA YANG TERDAMPAK COVID - 19 BERDASARKAN ASAS REBUS SIC STANTIBUS - Dominikus Savio Kung, (2021)
This paper discusses how the "rebus sic stantibus" principle protects Indonesian migrant workers affected by the COVID-19 pandemic. What are the protections and solutions provided by the "rebus sic stantibus" principle to Indonesian migrant workers affected by the COVID-19 pandemic. "rebus sic stantibus" can be the basis for terminating or delaying the entry into force of an international agreement. The principle of "rebus sic stantibus" can also be the basis for renegotiating work agreements between employers and Indonesian migrant workers due to the COVID-19 pandemic.